Teknologi Pengolahan Kopi Rempah Celup Sebagai Oleh-Oleh Khas Wisata Desa "Danau Suro Manggi" - M Zulkarnain Yuliarso; Ridha Rizki Novanda, M.Si; Basuki Sigit Priyono (DHARMA RAFLESIA, 2021)
To support government programs in rural economic development, it is necessary to apply appropriate technology that is tailored to the problems faced by the community related to coffee processing. Therefore, the planned service activities that will be carried out are to assist the community to create the latest superior products from Purwodadi Village. The aims of this research for: 1) Introduce the technology of making coffee spice dip, 2) Introduce how to do hygienic  packaging, 3) Introduce how to determine the cost of production and the selling price, and 4) Carry out one element of Higher Education Tri Dharma, namely Community Service. The service method is done by counseling, introducing technology, and applying technology. This dedication activity has introduced the technology of making coffee spice dip. Carrying out these service activities, in general, can provide knowledge and skills of processing coffee into coffee spice dip. The ability to determine cost of goods is also done well. There has been a change in knowledge, attitudes, and skills of the target group after the science and technology service activities were carried out .